2009
DOI: 10.1007/s12892-009-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N fertilizer top-dressing on N accumulation and N2 fixation of supernodulating soybean mutant

Abstract: Increased application of nitrogen (N) fertilizer top-dressing during growth is an effective option for enhancing N supply to soybean plants. SS2-2 was characterized by the superior ability of symbiotic N2 fixation at the level of 30 kg N ha -1 . But, the response of nitrogen fixation ability of supernodulating soybean mutant, SS2-2, to N fertilizer application rate remains unclear. The objective of this experiment was to compare the response of N fertilizer top-dressing on N accumulation and N2 fixation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Slow plant growth and smaller leaves observed were in accordance with the opinion of (Bacanamwo and Purcell, 1999), who reported retardation of leaf expansion, is an indicator as an early response to flooding. Many studies have reported a greater reduction of yield when plants were treated with excess water at a late growth stage than an early stage (Oosterhuis et al, 1990;Rhine et al, 2010;Scott et al, 1990;Youn et al, 2008). In some cases, it has even been suggested that the influence of flooding during early vegetative period is negligible (Rhine et al, 2010) because the slower early growth was more-or-less recovered during the late growing period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow plant growth and smaller leaves observed were in accordance with the opinion of (Bacanamwo and Purcell, 1999), who reported retardation of leaf expansion, is an indicator as an early response to flooding. Many studies have reported a greater reduction of yield when plants were treated with excess water at a late growth stage than an early stage (Oosterhuis et al, 1990;Rhine et al, 2010;Scott et al, 1990;Youn et al, 2008). In some cases, it has even been suggested that the influence of flooding during early vegetative period is negligible (Rhine et al, 2010) because the slower early growth was more-or-less recovered during the late growing period.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a high water table on yield were studied by Shimada et al (1997), who showed a 50% reduction, in seed yield when the water table rose to −15 cm because of heavy precipitation. In soybean, N 2 fixation is considered to be more sensitive to flood conditions than biomass production (Bacanamwo and Purcell, 1999;Buttery, 1987;Youn et al, 2008).This suggests that the enhancement of nitrogen (N) availability in the soil may help to ameliorate growth reduction by excess water. Also, inhibited leaf area development seems to be a primary factor that causes reduced biomass accumulation under excess water during the early stages of plant growth (Sugimoto et al, 1988;Furuhata et al, 2011) measure to maintain productivity in fields that are prone to excess water.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two soybean lines of different maturity groups (II-IX) and genetic backgrounds were selected for this study based on their potential N 2 fixation, nodulation, and higher yield in order to investigate the association of growth stages and N 2 fixation (Table 1). Additionally, three checks were included; the nonnodulating soybean cultivars Nitrasoy (Burton, Israel, & Bishop, 2006) and D68-099 (Hartwig, 1994) for estimating the amount of N derived from fixation as well as the supernodulating mutant SS2-2 (Youn et al, 2008;Youn et al, 2009) for evaluating the levels of N 2 fixation.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Physiologically, soybean's growth has a high nitrogen (N) demand that is required mainly for protein synthesis. For example, a maximal daily uptake of 4.6 kg ha -1 is required at the R4 (full pod) stage (Bender et al, 2015) and approximately 300 kg N is needed to produce 3 t ha -1 of soybean (Youn et al, 2009). In an environment that is ideal for crop's growth, especially for soybean, biological nitrogen fixation (BNF) can fulfil 50% of soybean's total N demand (Bender et al, 2015).…”
Section: Introductionmentioning
confidence: 99%